Metabolic evaluation of children with global developmental delay - So-Hee Eun; Si Houn Hahn (Korean Journal of Pediatrics, 2015)
Global developmental delay (GDD) is a relatively common early-onset chronic neurological condition, which may have prenatal, perinatal, postnatal, or undetermined causes. Family history, physical and neurological examinations, and detailed history of environmental risk factors might suggest a specific disease. However, diagnostic laboratory tests, brain imaging, and other evidence-based evaluations are necessary in most cases to elucidate the causes. Diagnosis of GDD has recently improved because of remarkable advances in genetic technology, but this is an exhaustive and expensive evaluation that may not lead to therapeutic benefits in the majority of GDD patients. Inborn metabolic errors are one of the main targets for the treatment of GDD, although only a small proportion of GDD patients have this type of error. Nevertheless, diagnosis is often challenging because the phenotypes of many genetic or metabolic diseases often overlap, and their clinical spectra are much broader than currently known. Appropriate and cost-effective strategies including up-to-date information for the early identification of the "treatable" causes of GDD are needed for the development of well-timed therapeutic applications with the potential to improve neurodevelopmental outcomes.